Study on fractional vegetation cover dynamic in the Yellow River Basin, China from 1901 to 2100 - Jian, Shengqi; Shi, Sijia; Cui, Jingkai; Zhu, Tiansheng; Hu, Caihong (Frontiers in Forests and Global Change, 2023)
The increasingly serious climate change makes the vegetation change dynamically. At the same time, the dynamic change of vegetation not only has a feedback effect on climate change, but also affects the hydrological cycle process. Therefore, understanding the change of vegetation and its response to climate change is the priority to predict future climate change and study the impact of vegetation change on hydrological cycle. In this study, the Yellow River Basin in China is the study area. Based on the analysis of the evolution characteristics of meteorological elements and fractional vegetation cover (FVC), the delta downscaling Coupled Model Intercomparison Project Phase 6 (CMIP6) models are optimized. The empirical orthogonal function (EOF) and singular value decomposition (SVD) method are used to study the impact of climate change on vegetation in the Yellow River Basin. The results show that: (1) In the four scenarios (SSP126, SSP245, SSP370, SSP585), FVC in the Yellow River Basin from 2022 to 2100 shows an upward trend, SSP370 (0.017 10a-1)>SSP126 (0.014 10a-1)>SSP245 (0.0087 10a-1)>SSP585 (0.0086 10a-1). Spatially, FVC in most regions of the Yellow River Basin show an increasing trend under the four scenarios, and the degraded areas are concentrated in a small part of the source area of the Yellow River. (2) There is a significant positive correlation between FVC and precipitation (Pre) and temperature (Tem) under four scenarios in the Yellow River Basin from 2022 to 2100. Under the same scenario, the annual average temperature can be regarded as the dominant factor of FVC change in the Yellow River Basin. In different scenarios, the impacts of climate change on FVC under the high emission scenarios are greater than those under low emission scenarios. This study will help to better understand the response of vegetation to climate change and provide a scientific basis for formulating ecological protection measures to cope with future climate change in the Yellow River Basin.